PS-InSAR derived deformation study in the Kachchh, Western India - Rakesh K. Dumka; D. SuriBabu; Kapil Malik; Sandip Prajapati; P. Narain (Applied Computing and Geosciences, 2020)
The accumulation of crustal strain towards the western part of India, especially in the Kachchh Rift basin, is making one of the most seismically active parts of the Indian plate. Several strong to major earthquakes, including the recent 2001 (M7.7) Bhuj earthquake, were triggered in the Kachchh rift basin during the last two centuries. Therefore, in the present study, we have attempted to quantify crustal deformation towards the eastern part of mainland Kachchh using PSInSAR and GPS data from 2014 to 2019. The average LOS displacement of 4.3 ​mm/yr has been observed along the eastern segment of the Katrol Hill Fault (KHF). The deformation in this part can be correlated with the accumulation of strain along the hanging wall side of the south-dipping KHF. The accumulated strain is reflected in the form of seismic activity in this part and highlights the importance of the KHF zone for seismic hazard analysis. The PS-InSAR results are in good correlation with the GPS results of this part.